Glottis effects on the cough clearance process simulated with a CFD dynamic mesh and Eulerian wall film model. Issue 12 (10th September 2017) - Paz, Concepción; Suárez, Eduardo; Parga, Oscar; Vence, Jesús
Abstract: In this study, we have reproduced the cough clearance process with an Eulerian wall film model. The simulated domain is based on realistic geometry from the literature, which has been improved by adding the glottis and epiglottis. The vocal fold movement has been included due to the dynamic mesh method, considering different abduction and adduction angles and velocities. The proposed methodology captures the deformation of the flexible tissue, considers non-Newtonian properties for the mucus, and enables us to reproduce a single cough or a cough epoch. The cough efficiency (CE) has been used to quantify the overall performance of the cough, considering many different boundary conditions, for the analysis of the glottis effect. It was observed that a viscous shear force is the main mechanism in the cough clearance process, while the glottis closure time and the epiglottis position do not have a significant effect on the CE. The cough assistance devices improve the CE, and the enhancement rate grows logarithmically with the operating pressure. The cough can achieve an effective mucus clearance process, even with a fixed glottis. Nevertheless, the glottis closure substantially improves the CE results.